Implementasi Mediasi terhadap Perkara Perceraian di Pengadilan Agama Kabupaten Simalungun - Rayani Saragih (Jurnal SOMASI (Sosial Humaniora Komunikasi), 2020)
Mediation as a mechanism for decision making/peace agreement becomes the main authority of the parties to the dispute and maintains good relations. Mediation is fair because each party negotiates a solution to the problem with a win-win solution. Through Supreme Court Regulation (PerMA) No. 01 of 2008 concerning Mediation, mediation has been integrated in the court system. Mediation according to Article 1 paragraph 7 Perma No. 01 of 2008 is a way to resolve disputes through a negotiation process to obtain the agreement of the parties with the assistance of a mediator. Any decision of a judge who is not mediated first, then the decision is considered null and void by law. Divorce is the termination of the relationship between husband and wife both divorce and divorce. Before the judge decides the divorce case, mediation between parties is first carried out. The success of mediation is very minimal in divorce cases, this can be seen from the still many divorce cases in the court. This is an urgency in this study, where the application of mediation in divorce cases, especially in the District of Simalungun District. This research is a normative juridical research with literature study data collection techniques by examining literature-literature and analyzing regulations that are relevant to this research. The results of this study are expected to determine the implementation of mediation divorce cases in the Simalungun District Religious Court.